LG-ESSs and HG-ESSs: underlying molecular alterations and potential therapeutic strategies - Li, Chunhui; Wang, Chunhong (Journal of Zhejiang University. B. Science, 2021)
Endometrial stromal tumors (ESTs) include endometrial stromal nodule (ESN), low-grade endometrial stromal sarcoma (LG-ESS), high-grade endometrial stromal sarcoma (HG-ESS), and undifferentiated uterine sarcoma (UUS). Since these are rare tumor types, there is an unmet clinical need for the systematic therapy of advanced LG-ESS or HG-ESS. Cytogenetic and molecular advances in ESTs have shown that multiple recurrent gene fusions are present in a large proportion of LG-ESSs, and HG-ESSs are identified by the tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein epsilon ( YWHAE )-family with sequence similarity 22 ( FAM22 ) fusion. Recently, a group of ESSs harboring both zinc finger CCCH domain-containing protein 7B ( ZC3H7B )-B-cell lymphoma 6 corepressor ( BCOR ) fusion and internal tandem duplication (ITD) of the BCOR gene have been provisionally classified as HG-ESSs. In this review, we firstly describe current knowledge about the molecular characteristics of recurrent aberrant proteins and their roles in the tumorigenesis of LG-ESSs and HG-ESSs. Next, we summarize the possibly shared signal pathways in the tumorigenesis of LG-ESSs and HG-ESSs, and list potentially actionable targets. Finally, based on the above discussion, we propose a few promising therapeutic strategies for LG-ESSs and HG-ESSs with recurrent gene alterations.